“The Kids Hate It, but We Love It!”: Parents’ Reviews of Circle - Cino, Davide (2020)
The contribution aims to present a critical analysis of Circle—a screen time management and parental control device—through the lens of parental mediation, children’s surveillance, and children’s rights to online participation. Circle promises to sell parents peace of mind by allowing them to monitor their children’s online activities. In order to investigate how parents themselves understand Circle, we conducted a quantitative and qualitative content analysis of a sample of 154 parental reviews about the device on Amazon and Searchman by parents of children from early childhood to adolescence, with respect to perceived advantages and disadvantages of the device, parenting styles, and (the absence of) children’s voice and agency. Results suggest an ambivalent relationship between parents and the device. Most reviews adhere to the dominant discourses on ‘screen time,’ framing children’s ‘intimate surveillance’ as a good parenting practice, and emphasize the need for the ‘responsible parents’ to manage their children’s online experiences with the aid of Circle. Others, in turn, criticize the device for failing to enable fine grained monitoring, while few reported the device could dismiss children’s voice and cause conflicts in the households. Overall, findings suggest that parental control devices may promote restrictive mediation styles hindering children’s voice and their exploratory and participatory agency online.